A multi-scale approach to assess the effect of groundwater extraction on Prosopis tamarugo in the Atacama Desert. (August 2016) - Decuyper, Mathieu; Chávez, Roberto O.; Copini, Paul; Sass-Klaassen, Ute
Abstract: Groundwater-dependent ecosystems occur in arid and semi-arid areas worldwide and are sensitive to changes in groundwater availability. Prosopis tamarugo Phil, endemic to the Atacama Desert, is threatened by groundwater overexploitation due to mining and urban consumption. The effect of groundwater depletion on two representative sites (low -and high-depletion) was studied using a multi-scale approach, combining remote sensing based estimations of canopy growth and water condition, and tree-ring based analysis of stem growth. On the stand level two NDVI (Normalized Difference Vegetation Index) -derived parameters: NDVI in winter and the difference between NDVI in summer and winter showed significant negative trends in the high-depletion site, indicating drought stress. Radial stem growth of viable P. tamarugo trees was 48% lower in the high-depletion site. At the tree level, the Green Canopy Fraction (GCF) also indicated drought stress since a larger percentage of trees fell within lower GCF classes. Groundwater depletion of 3 m, reaching a groundwater depth of >10 m, increased drought stress, and led to reduced growth in viable trees. Viable trees may be able to adapt to the drop in groundwater levels by increasing root growth, whereas for non-viable trees, the effects might be detrimental. Highlights: Analysis of groundwater depletion in the Atacama Desert; the effects on tree growth. Remote sensing metrics indicated reduced crown viability and growth. Groundwater depletion resulted in a decrease of 48% radial stem growth.